2007
DOI: 10.1016/j.chemosphere.2006.11.061
|View full text |Cite
|
Sign up to set email alerts
|

Effect of arsenic on photosynthesis, growth and yield of five widely cultivated rice (Oryza sativa L.) varieties in Bangladesh

Abstract: Abstract:2 A glass house experiment was conducted to investigate the effect of soil arsenic on photosynthetic pigments, Chlorophyll-a and -b, and their correlations with rice yield and growth. The experiment was designed with three replications of six arsenic treatments viz. control, 10, 20, 30, 60, 90 mg of As kg Well correlations were observed between chlorophyll content and rice growth and yield suggesting that arsenic toxicity affects the photosynthesis which ultimately results in the reduction of rice gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
46
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 243 publications
(56 citation statements)
references
References 20 publications
(13 reference statements)
9
46
1
Order By: Relevance
“…1). Similar results have been presented by Rahman et al (2007) and Khan et al (2010), who found that the total As concentration differed by a factor of 3–9 between husks and de-husked grains. However, our investigation found the opposite of that trend in two out of three LAR varieties sampled, where the total As concentration in the de-husked grains was up to 2-fold higher than in the husks (Fig.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…1). Similar results have been presented by Rahman et al (2007) and Khan et al (2010), who found that the total As concentration differed by a factor of 3–9 between husks and de-husked grains. However, our investigation found the opposite of that trend in two out of three LAR varieties sampled, where the total As concentration in the de-husked grains was up to 2-fold higher than in the husks (Fig.…”
Section: Resultssupporting
confidence: 90%
“…The As concentration in the de-husked grains and husks of HYV rice has been found to range between 0.59–0.81 and 1.7–6.2 mg kg −1 , respectively (Rahman et al 2007; Khan et al 2010). As the husk tissue (the external part of the grain) comprises 21–30% of the whole weight of the rice grain, this implies that most of the As ends up in the husk.…”
Section: Introductionmentioning
confidence: 99%
“…Actually, variations on chlorophyll content depend not only on the applied As concentration, but also on its speciation, the time of contact, the plant species studied, and others. In literature, an inverse correlation between As concentration and chlorophyll content has been reported for relatively high As concentration (5 mg kg À1 in solution and 30 mg kg À1 in soils) (Azizur Rahman et al, 2007;Stoeva and Bineva, 2003;Stoeva et al, 2005). However, in some cases, an opposite behavior was found (Shaibur and Kawai, 2009;Sánchez-Viveros et al, 2011).…”
Section: Arsenic Effects On Photophysical Propertiesmentioning
confidence: 88%
“…Those elements inhibit chlorophyll and carotenoid biosynthesis and retard the incorporation of these pigments in photosystems (Stobart et al, 1985;Caspi et al, 1999;Boswell et al, 2002;Azizur et al, 2007). The presence of heavy metal and metalloid enrichment in the mineralized area restrained the growth of cells and resulted in declines in pigment contents of plants.…”
Section: Physiological Parameters and Chemical Compositions In Pigmentmentioning
confidence: 95%